The Effect Of Online Customer Reviews And Ratings On Consumer Purchase Decisions On Shopee E-Commerce - Ona Lisa; Silvia; Shafratul Husna; Dara Sabena; Iskandar (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to determine the influence of online customer reviews and online customer ratings on consumer purchasing decisions on Shopee e-commerce. The research uses a quantitative approach with purposive sampling technique involving 110 respondents in Bireuen Regency. Data were collected using questionnaires and analyzed using multiple linear regression. The results indicate that online customer reviews have a positive and significant effect on purchasing decisions, as evidenced by the t-value of 5.863 > 1.982 and a significance level of 0.000 < 0.05. Similarly, online customer ratings also significantly influence purchasing decisions with a t-value of 2.248 > 1.982 and a significance level of 0.027 < 0.05. Simultaneously, both variables have a significant effect on consumer purchasing decisions, indicated by the F-value of 64.235 > 3.08. These findings show that online customer reviews and ratings play an essential role in shaping consumer trust and purchasing decisions on Shopee.